MOTIVASI DAN KECERDASAN EMOSIONAL DAN IMPLIKASINYA DALAM PEMBELAJARAN - MAIDIL LAILI (JURNAL PENDIDIKAN ROKANIA, 2019)
Intelligence gives the biggest influence on a child's learning progress. It is needed a certain intelligence in order to be success including intellectual intelligence (IQ). But, the intellectual intelligence can not guarantee the success of someone's life. Daniel Goleman, the professor at Harvard University, in his book about Emotional Intelligence, explains that there are other factors determine the success of someone, one of them is emotional intelligence. Emotional intelligence is a number of capabilities and skills related to the development of social relations with the environment refer to the ability to recognize the self and others, the ability to motivate oneself, and the ability to control emotions and in relationships with others. Emotional intelligence has the biggest role in determining the success of someone's life, especially when they are still in the process of formal education shown by the success of learning achievement. Positive emotions can accelerate the learning process and achieve better learning outcomes. Therefore, the successful learning must begin by creating positive emotions in students themselves. To create positive emotions on students themselves can be done in various ways, such as by creating a fun learning environment and excitement of learning.